Genese og funktion - offeret ifølge Walter Burkert - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 1992)
Introduction to Walter Burkert's theory of the origin and function of animal sacrifice, with some remarks on it similarities with and differences to the alternataive theory of René Girard.